Tribological and corrosion behavior of Al2O3 interlayer reinforced friction stir welded AA6082-T6 joints - Abousoufiane Ouis; Mohamed I. A. Habba; Mohamed M. Z. Ahmed; Waheed S. Barakat (Scientific Reports)
Abstract Friction stir welding (FSW) of thick extruded AA6082-T6 aluminum alloy plates presents challenges in maintaining optimal mechanical and corrosion properties. This study investigated the effects of incorporating Al₂O₃ interlayer reinforcements on the microstructural, tribological, and corrosion behaviors of FSW joints. AA6082-T6 plates were friction stir welded with Al₂O₃ interlayer strips at various levels of 0, 4, 8, and 12 vol%. The resulting joints were characterized using optical microscopy, electron microscopy, X-ray diffraction, hardness testing, potentiodynamic polarization, and pin-on-disk wear tests. The Al₂O₃ reinforcement led to grain refinement, increased dislocation density, and enhanced microstrain in the weld zone. The relative density decreased with an increase in the Al₂O₃ content. The Vickers hardness improved systematically across all thicknesses of the reinforced joints, with the highest values observed in the 12 vol% Al₂O₃ specimen. The corrosion resistance of the reinforced joints improved significantly, approaching that of the base material. The wear resistance was enhanced in the reinforced joints with 8 vol% Al₂O₃ specimen consistently showing the highest enhancement ratios under various load conditions. The incorporation of Al₂O₃ interlayer reinforcements effectively mitigated the negative effects of FSW on AA6082-T6 joints, enhancing their microstructural, mechanical, tribological, and corrosion properties. Optimal performance was achieved with 8 vol% Al₂O₃ reinforcement, balancing improvements in hardness, wear resistance, and corrosion behavior.